2022
DOI: 10.1111/dpr.12597
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities with social inclusion and community‐based water management in Solomon Islands

Abstract: Motivation: Rural water services are poor in Pacific Island countries (PICs); ineffective water management (WM) is one of the key reasons. Greater social inclusion in WM groups is a key goal of Sustainable Development Goal (SDG) 6, but there is a lack of data on the make-up of WM groups and what appropriate and effective inclusivity in WM looks like in the region. Purpose: This article contributes to filling these gaps by examining national community WM policy and the attributes and activities of rural WM grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In community management, the service of living resources is crucial. Love, M. W et al pointed out that the low level of water services in rural communities in the middle of the Pacific Island countries is an important manifestation of the backwardness of community management and suggested that the service indicators of the community can be greatly strengthened through the effective supply of water resources [16]. Shoeb-Ur-Rahman, M et al made a discursive analysis of management conflicts in tourism communities, pointing out that social capital often interfered excessively with community co-management programs in tourism community development and proposed a community decision-making approach based on multiple equilibria [17].…”
Section: Relevant Studiesmentioning
confidence: 99%
“…In community management, the service of living resources is crucial. Love, M. W et al pointed out that the low level of water services in rural communities in the middle of the Pacific Island countries is an important manifestation of the backwardness of community management and suggested that the service indicators of the community can be greatly strengthened through the effective supply of water resources [16]. Shoeb-Ur-Rahman, M et al made a discursive analysis of management conflicts in tourism communities, pointing out that social capital often interfered excessively with community co-management programs in tourism community development and proposed a community decision-making approach based on multiple equilibria [17].…”
Section: Relevant Studiesmentioning
confidence: 99%